Plant tissue culture and transformation techniques - Sharma, Balram; Centre for Science and Technology of the Non-Aligned and Other Developing Countries (Delhi : Daya Pub. House, 2008)
Contributed articles.
"Centre for Science & Technology of the Non-Aligned and Other Developing Countries (NAM S&T Centre)."
Includes bibliographical references.
Keywords: Plant tissue culture -- Congresses; Plant genetic transformation -- Congresses; Plant biotechnology -- Developing countries -- Congresses